Antioxidant Activity of Nipah Endophytic Fungi (Nypha fruticans Wurmb) from Tanjung Jabung Timur Jambi - Fitratul Aini; Hasnaul Maritsa; Hesti Riany (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2019)
Nipah or Nypa fruticans Wurmb is a member of the Palmae tribe that lives in the Mangrove ecosystem and is known to have rich bioactive sources, one of which is antioxidants. The ability of N. fruticans as an antioxidant is also possible for endophytes associated with N. fruticans. This study aims to obtain endophytes that live in N. fruticans leaf tissue and find out their ability as antioxidant agents using synthetic free radicals 2.2 diphenil-1-pikrilhidrazil (DPPH). Samples taken at Nipah Panjang Tanjung Jabung Timur, Isolation and production were carried out at the Jambi University Faculty of Science and Technology Engineering and Biotechnology Laboratory, absorbance measurements using UV-VIS at λ 517 nm at the Jambi University CRC. The antioxidant activity of isolates was shown from the value of Inhibitor Concentration (IC50) which caused 50% loss of DPPH free radicals. From the results it was obtained that the six isolates (DN01, DN02, DN02, DN03, DN04, DN05, and DN06) value the antioxidant activity of endophytic extracts lower than vitamin C activity and still classified as weak. Even though endophytic Nypa fruticans are very weak, N. fruticans endophytic in all treatment concentrations still have the ability as antioxidants and optimization methods are needed to get good antioxidant values. Keywords: Mangrove, Nypa fruticans Wurmb, endophytes, antioxidants, DPPH